2022
DOI: 10.1136/jitc-2021-004381
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle delivery of miR-21-3p sensitizes melanoma to anti-PD-1 immunotherapy by promoting ferroptosis

Abstract: BackgroundAlthough anti-programmed cell death protein 1 (PD-1) immunotherapy is greatly effective in melanoma treatment, low response rate and treatment resistance significantly hinder its efficacy. Tumor cell ferroptosis triggered by interferon (IFN)-γ that is derived from tumor-infiltrating CD8+ T cells greatly contributes to the effect of immunotherapy. However, the molecular mechanism underlying IFN-γ-mediated ferroptosis and related potentially promising therapeutic strategy warrant further clarification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…Therefore, the intervention of ferroptosis is promising in restraining melanoma progression and increasing the effectiveness of either targeted therapy or immunotherapy. Some studies have demonstrated the upstream regulatory mechanism of ferroptosis in melanoma before [ 14 , 15 , 16 ], and we previously reported that CAMKK2 and miR-21-3p were critical regulators of melanoma cell ferroptosis through the regulation of AMPK-Nrf2 and TXNRD1, respectively [ 8 , 49 ]. Herein, we proved that Wnt/β-catenin signaling was also implicated in melanoma cell ferroptosis, extending the upstream regulatory network of ferroptosis in melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the intervention of ferroptosis is promising in restraining melanoma progression and increasing the effectiveness of either targeted therapy or immunotherapy. Some studies have demonstrated the upstream regulatory mechanism of ferroptosis in melanoma before [ 14 , 15 , 16 ], and we previously reported that CAMKK2 and miR-21-3p were critical regulators of melanoma cell ferroptosis through the regulation of AMPK-Nrf2 and TXNRD1, respectively [ 8 , 49 ]. Herein, we proved that Wnt/β-catenin signaling was also implicated in melanoma cell ferroptosis, extending the upstream regulatory network of ferroptosis in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, two studies have highlighted that the induction of tumor cell ferroptosis triggered by IFN-γ resulting from infiltrated CD8 + T-cells mediates the influence of melanoma immunotherapy [ 12 , 13 ]. Our previous investigations proved that miR-21-3p and CAMKK2 regulated the TXNRD1 and AMPK-Nrf2 axes, respectively, to mediate the execution of melanoma cell ferroptosis [ 8 , 49 ]. Either nanoparticle delivery of miR-21-3p or systemic administration of a CAMKK2 inhibitor could prominently enhance the effectiveness of anti-PD-1 immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In immunotherapy, IFN-γ is the main effector that triggers ferroptosis in tumor cells. Guo et al (2022) found that one of the important mechanisms for ferroptosis induced by IFN-γ in melanoma is the activation of the ATF3/ miR-21-3p/TXNRD1 axis, and blocking this axis attenuates ferroptosis and therapeutic effect of IFN-γ, which indicates that the overexpression of miR-21-3p may play a synergistic role with anti-PD-1 immunotherapy. In order to verify whether miR-21-3p can enhance the effect of anti-PD-1 in vivo, the researchers constructed miR-21-3p-loaded gold nanoparticles (miR-21-3p-AuNp), injected them into melanoma transplanted mice, and injected anti-PD-1 for immunotherapy.…”
Section: Application and Effect In Treatmentmentioning
confidence: 97%
“…This indicated that miR-21 could play a role in ferroptosis [ 93 ]. Interestingly, delivery of miR-21-3p to melanoma cell lines was found to promote interferon-gamma (IFN-γ)-mediated ferroptosis by targeting thioredoxin reductase 1 and elevating ROS generation [ 94 ].…”
Section: Microrna-21 In Cell Deathmentioning
confidence: 99%